Comparative analyses of thoracic radiographs and bronchoalveolar lavage of dogs and cats with chronic bronchial diseases - Mariana Pavelski (Semina: Ciências Agrárias, 2017)
There is a high incidence of bronchitis and asthma cases in veterinary medicine. Thoracic radiographs and bronchoalveolar lavage (BAL) are commonly performed for de¿nitive diagnosis in dogs and cats with suspected bronchitis and asthma. It is believed that a combination of diagnostic tools is the best choice to achieve a diagnosis. The aim of this study was to evaluate the ef¿cacy of thoracic radiographs and BAL in the diagnosis of chronic bronchial disease (CBD) in dogs and cats and whether there is any speci¿c radiographic ¿nding that could inÀuence the indication for bronchoalveolar lavage. It was performed a cross-sectional, prospective, observational study including forty client-owned dogs and cats with lower respiratory tract signs and positive radiographic opacities that were evaluated with BAL followed by cytology and culture. The radiographic results compared with BAL culture showed a sensitivity of 38%, speci¿city of 95% and accuracy of 65% in detecting patients with pneumonia associated with chronic bronchial disease. Thoracic radiographs were effective in diagnosing 65% of the patients, radiographs plus BAL cytology diagnosed 75% of patients and the combination of radiographs, BAL cytology and culture diagnosed 95% of the patients with chronic bronchial disease. In conclusion, the combination of radiographic examination with BAL followed by cytological and microbiological analyses increases diagnostic success in CBD.